Analisis AIDS Stigmation of Adolescents In Medan City - Putra Apriadi Siregar (Universitas Muhammadiyah Malang, 2021)
AIDS is a disease that is still high in all parts of the world, including Indonesia. Gender is a factor in the occurrence of stigmatization in adolescents. This study aimed to determine the stigma factor for HIV/ AIDS among adolescents in Medan City. This research is a quantitative descriptive study using a cross-sectional study design with a quantitative approach. This research was conducted in Medan City conducted from August to December 2020. The data source in this study was primary data obtained from interviews. Collecting data by direct interviews using a structured questionnaire. Analysis of the data in this study using descriptive analysis and crosstab using the SPSS version 22 program. The results showed that as much54 girls do not want to swim in the same swimming pool as HIV/ AIDS, 55 girls do not want to eat/drink a plate with HIV/ AIDS, 46 girls do not want to use the toilet with HIV/ AIDS, 36 girls do not want to touch their skin with HIV/ AIDS. HIV/ AIDS, 52 teenagers do not want to sleep together with HIV/ AIDS, and 57 young women do not want to wear the same clothes as HIV/ AIDS. It was concluded that female adolescents are more likely to stigma on people living with HIV/ AIDS than male adolescents. It is necessary to carry out socialization and health education to adolescents to eliminate the stigmatization of HIV/ AIDS.